The convoluted process of diagnosing pulmonary mycosis caused by Exophiala dermatitidis: a case report - Li, Zhengtu; Tang, Jianli; Zhu, Jinping; Xie, Mingzhou; Huang, Shaoqing; Li, Shaoqiang; Zhan, Yangqing; Zeng, Weiqi; Xu, Teng; Ye, Feng (BMC infectious diseases, 2022)
Etiological diagnosis is a key step in the treatment of patients with rare pulmonary mycosis, and the lack of understanding of this disease and lack of specific markers for the detection of rare species, such as Exophiala dermatitidis, add to the difficulty in diagnosing the condition. Therefore, improving the diagnostic strategies for this disease is very important. A 52-year-old man presented with cough, sputum production and hemoptysis; chest computed tomography (CT) revealed multiple bilateral lesions. The pathogen was unable to be identified after three biopsies. Subsequently, we performed combined tissue metagenomic next-generation sequencing (mNGS). The results of mNGS and a good therapeutic response helped to identify the causative pathogen as Exophiala dermatitidis. Finally, the patient was diagnosed with Exophiala dermatitidis pneumonia. Combining molecular techniques, such as mNGS, with clinical microbiological tests will improve the rate of positivity in the diagnosis of rare fungal infections, and the importance of follow-up should be emphasized.